2006
DOI: 10.1007/11866763_6
|View full text |Cite
|
Sign up to set email alerts
|

Active Shape Models for a Fully Automated 3D Segmentation of the Liver – An Evaluation on Clinical Data

Abstract: Abstract. This paper presents an evaluation of the performance of a three-dimensional Active Shape Model (ASM) to segment the liver in 48 clinical CT scans. The employed shape model is built from 32 samples using an optimization approach based on the minimum description length (MDL). Three different gray-value appearance models (plain intensity, gradient and normalized gradient profiles) are created to guide the search. The employed segmentation techniques are ASM search with 10 and 30 modes of variation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 8 publications
(7 reference statements)
1
45
3
1
Order By: Relevance
“…Statistical form models learn the mean organ form with its variants from training data. Using even the current models, it can be shown that the work of segmentation can be significantly reduced for the liver [19] . …”
Section: Klauß M Et Al 3d-reconstructions In Pancreatic Carcinomamentioning
confidence: 99%
“…Statistical form models learn the mean organ form with its variants from training data. Using even the current models, it can be shown that the work of segmentation can be significantly reduced for the liver [19] . …”
Section: Klauß M Et Al 3d-reconstructions In Pancreatic Carcinomamentioning
confidence: 99%
“…A SSM is widely used for organ segmentation and its potential performance for liver segmentation has been shown [3] [4]. However, previous methods using SSM [3] [4] had the following problems: (1)There is essential limitation on reconstruction accuracy especially for diseased livers involving large deformations and lesions.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous methods using SSM [3] [4] had the following problems: (1)There is essential limitation on reconstruction accuracy especially for diseased livers involving large deformations and lesions. (2) Good initialization is required to obtain proper convergence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations